Centralized Smart Home Framework Monitoring for Power Savings - Setyawan, Gembong Edhi; Setiabudi, Agung; Muttaqin, Adharul; Ichsan, Mochammad Hannats Hanafi (Journal of Information Technology and Computer Science, 2016)
Abstract. Electrical energy has become a staple for humans. Almost all human activities always require electrical energy. To maintain the availability of electricity at any time, then it takes the process of global electricity savings. The electricity savings can be done in two ways, the first is the development of technology to make electric appliances that require low power for operation and the second is to improve human behavior in the use of electrical appliances (turning off electrical appliances when not in use). This research aims to create a centralized smart home that can help people to monitor the condition of electrical appliances in the house and turn off automatically when not being used. Besides this system could also be used in manual mode and be controlled remotely using a smartphone through the Internet. The system is made centrally so not only for the home but can be used for many homes. After application was implemented it can monitored which device is turned on or turned off.Keywords: Smart Home, Monitoring and Power Savings